Dialectization and use of resources in co-created ecologies: towards a new approach on contemporary e-learning - Forero Arango, Ximena; Zapata Duque, Jorge Fernando (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
This study delves into the importance of the teaching role in virtual education as a catalyst for interactions between the participants and the contents of the courses in co-created ecologies of learning. It was carried out at the Faculty of Communications and Philology of the University of Antioquia, a public institution with 219 years of history of training in face-to-face methodology. The investigation was carried out from an interpretive constructivist paradigm, with a qualitative approach and a Grounded Theory design, whose objective was to propose a pedagogical model for virtual education in undergraduate level programs. This model was tested in a free course carried out through WhatsApp, and then in a regular undergraduate course in which the Meet, Classroom and WhatsApp tools were combined. The analysis of the data collected in these exercises suggests that the training spaces in which the teacher assumes a dialectizing role, using resources available online and in multiple languages, allow a greater flow of interactions in accordance with the concept of co-created ecologies. which integrated the personal learning environments of the participants, with those proposed by the University. Thus, it was demonstrated that it is possible to propose new ways of conceiving and putting into practice higher education in undergraduate virtual methodology, beyond the practices that prevailed in the context of the so-called remote education in emergency.